Screening and Whole Genome Sequencing of SARS-CoV-2 Circulating During the First Three Waves of the COVID-19 Pandemic in Libreville and the Haut-Ogooué Province in Gabon - Lekana-Douki, Sonia Etenna; N'dilimabaka, Nadine; Levasseur, Anthony; Colson, Philippe; Andeko, Julia Cyrielle; Zong Minko, Ornella; Banga Mve-Ella, Octavie; Fournier, Pierre-Edouard; Devaux, Christian; Ondo, Bertrand Mve; Akombi, Falone Larissa; Yacka Mouele Bolo, Laurianne; et al. (Frontiers in Medicine, 2022)
Since the onset of the COVID-19 pandemic, the SARS-CoV-2 viral dynamics in Africa have been less documented than on other continents. In Gabon, a Central African country, a total number of 37,511 cases of COVID-19 and 281 deaths have been reported as of December 8, 2021. After the first COVID-19 case was reported on March 12, 2020, in the capital Libreville, the country experienced two successive waves. The first one, occurred in March 2020 to August 2020, and the second one in January 2021 to May 2021. The third wave began in September 2021 and ended in November 2021. In order to reduce the data gap regarding the dynamics of SARS-CoV-2 in Central Africa, we performed a retrospective genotyping study using 1,006 samples collected from COVID-19 patients in Gabon from 2020 to 2021. Using SARS-CoV-2 variant screening by Real-Time Quantitative Reverse Transcription PCR (qRT-PCR) and whole genome sequencing (WGS), we genotyped 809 SARS-CoV-2 samples through qRT-PCR and identified to generated 291 new genomes. It allowed us to describe specific mutations and changes in the SARS-CoV-2 variants in Gabon. The qRT-PCR screening of 809 positive samples from March 2020 to September 2021 showed that 119 SARS-CoV-2 samples (14.7%) were classified as VOC Alpha (Pangolin lineage B.1.1.7), one (0.1%) was a VOC Beta (B.1.351), and 198 (24.5 %) were VOC Delta (B.1.617.2), while 491 samples (60.7%) remained negative for the variants sought. The B1.1 variant was predominant during the first wave while the VOC Alpha dominated the second wave. The B1.617.2 Delta variant is currently the dominant variant of the third wave. Similarly, the analysis of the 291 genome sequences indicated that the dominant variant during the first wave was lineage B.1.1, while the dominant variants of the second wave were lineages B.1.1.7 (50.6%) and B.1.1.318 (36.4%). The third wave started with the circulation of the Delta variant (B.1.617). Finally, we compared these results to the SARS-CoV-2 sequences reported in other African, European, American and Asian countries. Sequences of Gabonese SARS-CoV-2 strains presented the highest similarities with those of France, Belgium and neighboring countries of Central Africa, as well as West Africa.